2016
DOI: 10.1007/s00221-016-4692-7
|View full text |Cite
|
Sign up to set email alerts
|

Nerve crush but not displacement-induced stretch of the intra-arachnoidal facial nerve promotes facial palsy after cerebellopontine angle surgery

Abstract: Little is known about the reasons for occurrence of facial nerve palsy after removal of cerebellopontine angle tumors. Since the intra-arachnoidal portion of the facial nerve is considered to be so vulnerable that even the slightest tension or pinch may result in ruptured axons, we tested whether a graded stretch or controlled crush would affect the postoperative motor performance of the facial (vibrissal) muscle in rats. Thirty Wistar rats, divided into five groups (one with intact controls and four with faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The pathological examination indicated that these cells often exhibit atypical mitosis (Machado et al, 2016). Patients with advanced cancer often exhibited severe systemic symptoms and high recurrence rate after surgical excision, causing a big challenge for cancer therapy (Bax et al, 2016;Bendella et al, 2016;Frohman et al, 2016). In view of the enormous harm caused by cancer, the development of new antitumor treatments has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological examination indicated that these cells often exhibit atypical mitosis (Machado et al, 2016). Patients with advanced cancer often exhibited severe systemic symptoms and high recurrence rate after surgical excision, causing a big challenge for cancer therapy (Bax et al, 2016;Bendella et al, 2016;Frohman et al, 2016). In view of the enormous harm caused by cancer, the development of new antitumor treatments has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current review, the rat (Bendella et al, 2016) and the rabbit model (Maurer and Mika, 1983;Lumenta et al, 1988;Widick et al, 1994;Braun and Richter, 1996;Telischi et al, 1999) seem to be the most feasible rodent models for manipulation of the intra-arachnoidal FN in the CPA. Mice were used for stereotactically guided injection of modified Schwann cells to create CPA-tumors (Bonne et al, 2016;Dinh et al, 2018;Chen et al, 2019).…”
Section: Anatomical Feasibility To Expose the Intracranial Facial Nerve In A Rabbit Animal Modelmentioning
confidence: 99%
“…Beside a proper head fixation, even when working under microscopic magnification, the amount of required maneuverability depends on the FN-reconstruction techniques used. The smallest animal reported in the current review, where cranial nerves of the CPA were manipulated, was the rat (Table 7; Mattsson et al, 1999;Burgette et al, 2012;Amine et al, 2014;Bendella et al, 2016;Bonne et al, 2016;Dinh et al, 2018;Chen et al, 2019), followed by the New Zealand rabbit or guinea pig (Table 8; Maurer and Mika, 1983;Lumenta et al, 1988;Levine et al, 1993;Widick et al, 1994;Braun and Richter, 1996;Telischi et al, 1999), cats, dogs and monkeys (Table 9; Chinn and Miller, 1975;Mangham and Miller, 1979;Sekiya et al, 1985Sekiya et al, , 1990Fisch et al, 1987;Sekiya and Moller, 1988;Lusk et al, 1990;Greiman and Lusk, 1991;Glasby et al, 1995). However, the rat model published by Amine et al (2014) and Burgette et al (2012) for intracranial FN injury required extensive petrous bone drilling, FN rerouting and removal of the cochlear structures to sufficiently expose the FN, on the other hand efficiently creating a post-operative intracranial FN palsy (Table 7).…”
Section: Experimental Animal Model For Intracranial Facial Nerve Lesionsmentioning
confidence: 99%
See 2 more Smart Citations